OTOMATISASI PENYEMPROTAN PESTISIDA PADA KUMBUNG JAMUR TIRAM PUTIH BERBASIS MIKROKONTROLLER - Nur Faridzi, Muhammad Alvin (Jurnal Elektro Kontrol (ELKON), 2024)
Oyster mushroom cages as a medium for cultivating oyster mushrooms, as cultivation media for oyster mushrooms, often face vulnerabilities to pest and disease attacks. Manual pesticide spraying methods require considerable time and effort, besides potentially posing hazardous pesticide exposure to humans. The proposed solution to tackle this challenge is an automated pesticide spraying system utilizing ESP32. In this system, ESP32 acts as a microcontroller controlling a 12V DC pump, relay, and misting nozzle. The RTC DS3231 is used to counter down time, so that spraying can be done automatically only when conditions match the settings. This research aims to develop and evaluate the effectiveness of an automated pesticide spraying system in mushroom farms using ESP32. Spraying is done every 3 days with a spraying duration of 20 seconds. Before the automatic spraying function activates, there are many thrips pests. After reaching the set point and spraying is performed, the number of thrips pests decreases. Thrips pests can disappear after the second spraying.Keywords: ESP32, Automation, Pesticide Spraying, White oyster mushroom cage, RTC DS3132